INDUKSI KALUS DAN EMBRIOGENESIS SOMATIK IN VITRO PADA LAMTORO (Leucaena leucocephala) - Yusri Sapsuha; Djoko Soetrisno; Kustantinah Kustantinah (Research Center for Biology-Indonesian Institute of Sciences, 2011)
This research is aimed to determine the effect of various concentrations (0, 1, 2, 3, 4 and 5 mg/l) of 2,4-D (dichloropenoxy acetic acid) on callus induction of Lamtoro (Leucaena leucocephala) and its somatic embryogenesis stimulated using different concentrations of 0, 0.5, 1.0, 1.5 and 2.0 mg/l of growth regulators, namely NAA (Naphthaleneacetic acid) and kinetin. Percentage of callus were measured and somatic embryogenesis from callus were subjected to description analysis. The results showed that callus percentage were varied from 29.34% (1 mg 2,4-D/l) at first week (white color and crumb) to 83.67% (4 mg 2,4-D/l) at fourth week (white yellowish color and compact), and embryo somatic varied from 19.33±2.52 (2 mg NAA and 0 mg kinetin/l) to 81.33±11.50 (1.5 mg NAA dan 2.0 mg kinetin/l). It can be concluded that optimum callus induction (83.67%) was recorded when concentration of 2,4-D was given at the rate of 4 mg/l. The largest number of embryos in concentration of 1.5 mg/l NAA and 2.0 mg/l kinetin, and embryo somatic 81.33±11.50.